TRANSLATION ANALYSIS OF THE STORY BOOK “AL QIROATU AR ROSYIDAH” FOR 10th GRADE STUDENTS OF RIYADHUSSHOLIHIN HIGH SCHOOL PANDEGLANG BANTEN (Universitas Negeri Semarang, 2023)
A student has many difficulties understanding, translating, and reading Arabic texts. This study aims to develop Arabic language skills, especially in translating, writing, reading, expanding Arabic vocabulary, and understanding the experienced phenomena. This qualitative descriptive research aims to discover the translation techniques for translating Arabic storybooks. Qualitative research produces descriptive data about the observed object in words or spoken words. The analysis findings show that seven of the twelve translation techniques suggested by Newmark are used in translating the Arabic text of the storybook “Al Qiroah Ar Rasyidah.” It is found fifteen data from the Arabic text in the storybook “Al Qiroah Ar Rasyidah,” which has been classified into types of translation techniques. Those synonymous translation techniques consist of four data (26.7%). Then, the modulation translation techniques consist of three data (20%). Two data are found using literal translation techniques (13.3%). The transference translation technique is applied in the two data (13.3%) who used the two data expansion translation techniques (13.3%). It also used transposition translation techniques in one data (6.7%). Then, the reduction translation technique is applied to one data 6.7%).